2014
DOI: 10.1515/commun-2014-0005
|View full text |Cite
|
Sign up to set email alerts
|

The older player of digital games: A classification based on perceived need satisfaction

Abstract: The current study aims to integrate the findings of previous research on the use of video games by older adults by applying the Uses & Gratifications (U&GT) paradigm (Blumler and Katz, 1974). A qualitative study was performed with 35 participants aged between 50 and 74, who were selected from a larger sample of 213. Based upon their primary playing motives and the gratifications they obtain from digital game play, a classification was developed, resulting in five categories of older adults who actively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 4 publications
6
55
0
Order By: Relevance
“…This study is not without known methodological limitations regarding problems in obtaining a representative sample of older adult players [6]. Of note, there is great heterogeneity in older people regarding their cognitive and physical abilities and their preferred leisure activities that were not addressed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is not without known methodological limitations regarding problems in obtaining a representative sample of older adult players [6]. Of note, there is great heterogeneity in older people regarding their cognitive and physical abilities and their preferred leisure activities that were not addressed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…First, learning to play and interact with fast-paced action video games can be very difficult and demotivating for older adults. Second, questionnaire and playtest studies have found that older adults generally dislike action video games, especially when featuring violent content [4,6-8]. Together, this leads to a situation where older adults, despite promising cognitive benefits, are less willing and motivated to play action video games, and thus less likely to follow through with action video game interventions [4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Based on an online survey of players of one casual video game, Whitbourne, Ellenberg, and Akimoto (2013) reported that gamers of all ages played primarily for social reasons, and older adults said that gameplay helped them to improve their visual and spatial skills and their response time. De Schutter and Malliet (2014) identified cognitive and social connectedness needs as two of five types of gameplay motivation identified by older adults but could not directly relate these to the types of satisfaction that their subjects described. Gerling et al (2015) and McLaughlin et al (2012) suggested that difficulties in learning and playing digital games are among the costs that discourage older adults from engaging in gameplay, but they do not specifically address the benefits perceived by those who have avoided or overcome these issues to become more frequent and/ or skilled players.…”
Section: Perceived Gameplay Benefits and Costsmentioning
confidence: 96%
“…Games satisfy a variety of needs for older adults (De Schutter, Brown, & Vanden Abeele, 2015;De Schutter & Malliet, 2014). Adults play games for many reasons, and their motivations vary with their previous game exposure and their physical and cognitive abilities (Brown, 2012(Brown, , 2014.…”
Section: Digital Games and Older Adultsmentioning
confidence: 99%
“…It is also a common means for grandparents and grandchildren to build relationships, enjoy each other's company, learn together, resolve problems collaboratively, and get close through mutual encouragement (Zhang & Kaufman, 2016a). Today, many younger people and older adults have integrated digital games into their daily leisure activities (De Schutter & Malliet, 2014). In 2015, 26% of game players in America were aged 50 and over (ESA, 2016).…”
Section: Intergenerational Digital Gameplaymentioning
confidence: 99%